An assessment of seawater intrusion overshoot using physical and numerical modeling. Issue 10 (9th October 2013) - Morgan, Leanne K.; Stoeckl, Leonard; Werner, Adrian D.; Post, Vincent E. A.
<x xml:space="preserve">Abstract</x> [1] In recent years, a number of numerical modeling studies of transient sea‐level rise (SLR) and seawater intrusion (SWI) in flux‐controlled systems have reported an overshoot phenomenon, whereby the freshwater‐saltwater interface temporarily extends further inland than the eventual steady state position. In this study, we have carried out physical sand tank modeling of SLR‐SWI in a flux‐controlled unconfined aquifer setting to test if SWI overshoot is a measurable physical process. Photographs of the physical SLR experiments show, for the first time, that an overshoot occurs under controlled laboratory conditions. A sea‐level drop (SLD) experiment was also carried out, and overshoot was again observed, whereby the interface was temporarily closer to the coast than the eventual steady state position. This shows that an overshoot can occur for the case of a retreating interface. Numerical modeling corroborated the physical SLR and SLD experiments. The magnitude of the overshoot for SLR and SLD in the physical experiments was 24% of the change in steady state interface position, albeit the laboratory setting is designed to maximize overshoot extent by adopting high groundwater flow gradients and large and rapid sea‐level changes. While the likelihood of overshoot at the field scale appears to be low, this work has shown that it can be observed under controlled laboratory conditions.